Pendampingan Metode Tilawati dalam Pembelajaran Membaca Al-Qur’an pada Siswa di SDIT Al Qonita - Ratih Nor Aila; Istiyati Mahmudah; Siti Romlah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This community service activity aims to improve students' Qur'an reading skills through the Tilawati method at SDIT Al Qonita. The community service method used is Participatory Action Research (PAR) which consists of planning, action, observation, and reflection stages. The subjects of the activity are students who are taking part in the Qur'an reading learning in volume 2 which is divided based on reading ability. The mentoring is carried out through classical learning, reading, explanation of tajweed, and strengthening the rhythm of reading. The results of the activity show that students are enthusiastic about participating in learning, actively imitating reading, and experiencing increased abilities even though they still have difficulties with certain letters. In addition, this mentoring also strengthens the capacity of teachers to continue the Tilawati practice continuously, so that the Tilawati method is proven effective in creating a pleasant learning atmosphere while getting students used to reading according to the rules of tajweed.